Kuruçay Höyük Kazı Buluntuları Üzerine Arkeobiyolojik Araştırmalar - Deniz, E.
Englische Zusammenfassung: Archaeobiological Studies on the Early Bronze Age and Chalcolithic Materials from Kuruçay Höyük Excavations.